2016
DOI: 10.1159/000445941
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Insulin Sensitizers on the Incidence of Dementia: A Meta-Analysis

Abstract: Background: Abundant evidence from epidemiological and clinical studies has proven that diabetes mellitus (DM) is correlated with an increased incidence of dementia and Alzheimer's disease (AD). Insulin resistance is considered to play an important role in the associations between DM and dementia. However, whether insulin sensitizer drugs are effective in preventing dementia still remains unclear. Methods: Electronic searches of PubMed, EMBASE, Google Scholar, and the ISI Web of Science were conducted to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 26 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…The concept of precision medicine is emerging in relation to the prevention and treatment of AD (33), and the abundant evidence of various AD phenotypes, of which the metabolic phenotype is one, suggests that it is extremely relevant in this field. A recent meta-analysis (34) indicated that insulin-sensitizer drugs, like metformin and thiazolidinediones, might be useful in the prevention of dementia in patients with diabetes. Whether there is a direct mechanistic link is still controversial, but evidence from rat studies has shown that the glucagon-like peptide 1 analog liraglutide, another insulin sensitizer, interacts directly with processes leading to amyloid plaques and neurofibrillary tangles, which are the two pathological hallmarks of AD (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of precision medicine is emerging in relation to the prevention and treatment of AD (33), and the abundant evidence of various AD phenotypes, of which the metabolic phenotype is one, suggests that it is extremely relevant in this field. A recent meta-analysis (34) indicated that insulin-sensitizer drugs, like metformin and thiazolidinediones, might be useful in the prevention of dementia in patients with diabetes. Whether there is a direct mechanistic link is still controversial, but evidence from rat studies has shown that the glucagon-like peptide 1 analog liraglutide, another insulin sensitizer, interacts directly with processes leading to amyloid plaques and neurofibrillary tangles, which are the two pathological hallmarks of AD (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic interventions seeking to enhance astrocytic lactate transport may provide a more fruitful endeavour. MCT1 knockout mice show deficits in long term memory (109) Metformin, the antidiabetic drug, has received a lot of attention with regards to its potential act as a novel therapeutic strategy in managing AD (112)(113)(114). This links into the emerging hypothesis that AD should be classed as a third type of diabetes (115,116).…”
Section: Relevance To Alzheimer's Diseasementioning
confidence: 99%
“…Current treatments only offer symptomatic improvement without stopping disease progression [8]. Therefore, identifying the risk factors for dementia is important for effectively preventing or postponing the onset of AD [9,10]. …”
Section: Introductionmentioning
confidence: 99%